Isolation and characterization of a new dsRNA virus from Wickerhamia fluorescens - Pospísek, M; Palková, Z; Korb, J; Vanĕk, D (Folia microbiologica, 1996)
Virus-like particles (VLPs) were isolated from the yeast Wickerhamia fluorescens strain CCY61-1-1. The VLPs are approximately 42 nm in diameter and contain only one species of dsRNA molecule. The apparent length of the dsRNA determined by native agarose gel electrophoresis was 4.6 kbp. Analysis of protein content of the VLPs showed them to contain one major capsid protein with an apparent molar mass of 74.5 kDa.
Keywords: RNA, Viral; molekulová hmotnost; dvouvláknová RNA; RNA, Double-Stranded; RNA virová; Totivirus; Yeasts; kvasinky; Electrophoresis, Agar Gel; elektroforéza v agarovém gelu; kapsida; Molecular Weight; Capsid